Penerapan Konsep Gamification Pada Aplikasi Pembelajaran Berbasis Android - Aditya Darmawan; Tri Sagirani; Julianto Lemantara (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
Baitul Hasanah Youth Mosque located on Asem Jajar Street, Tembok Dukuh Sub-District, Bubutan Sub-District, Surabaya City has several activities that are often carried out to study Islamic studies, sholawatan and khotmil quran. In the assessment activities, a reduction in the number of assumptions taken as a learning process is carried out. Mosque youth administrators want to bind members to keep getting religious knowledge every time they receive information technology assistance. This research is designed to create a Mobile Learning application that allows users to access learning content without being asked by place and place.Mobile Learning that will be built using the concept so that learning can be done every day with more interesting and motivating applications to do something that can be done to carry out these activities. The data source used in this study was canceled 10 user accounts that have been registered and email verified. Based on the results of trials on each function in the system shows that the application of learning by applying the concept of gamification to the Baitul hasanah mosque youth has been going very well and the results are in accordance with the system design.